Important attributes of corporate social responsibility - an exploratory assessment from Oman - Minnee, Flora; Shanka, Tekle (School of Marketing, Curtin Business School, 2008)
This paper reports the results of an exploratory investigation of consumers in Greater Moscat area of the Sultanate of Oman in regards to the important attributes that a socially responsible company should have in order to meet its social responsibility and corporate citizenship. An intercept survey of 153 participants (45% Omanis and 55% expatriates) revealed that a socially responsible company should have attributes such as safe products/services, appropriate treatment of employees, provision of reliable products/services, behave ethically, and committed to social responsibility. The 16 item attributes measured on 5-point Likert scale were represented by three components, namely community, organisation, and commitment and explained 62% of total variance. Whilst gender had no statistically significant difference on these three components, age, education, and nationality demographics showed statistically significant differences. Results were discussed with suggestions for further assessment of the larger sample of the Omani consumers located outside of the Greater Moscat area.